Short Term Outcome of Viral Encephalitis Cases Seen at a Tertiary Care Center in Bangladesh: Focus on Herpes Simplex Encephalitis - Kabir, Md Humayun; Amin, Md Ruhul; Phani, Ashok Kumar; Uddin, Mohammad Kamal; Karim, Mohammed Maksudul; Azam, Akramul; Alam Khandker, Md Mahabubul; Hassanuzzaman, Md (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Acute infective encephalitis is usually viral. Herpes Simplex Encephalitis (HSE) is the commonest sporadic acute viral encephalitis in the Western world. Management of HSE has been considerably improved by the availability of acyclovir therapy and rapid Polymerase Chain Reaction (PCR) based diagnostic assays. There is paucity of data regarding recent hospital incidence, acute mortality and morbidity of patients admitted with suspected viral encephalitis. The aim of this study was to determine the frequency of HSE confirmed by PCR assay in a sample of clinically diagnosed patients of viral encephalitis admitted in a tertiary care hospital of Bangladesh and to evaluate the short term outcome of these patients with a focus on HSE. Methods and materials: This hospital-based prospective observational study was carried out in Department of Neurology, Medicine and Pediatric Medicine of Chittagong Medical College Hospital from February 2017 to January 2018. Thirty eight clinically diagnosed patients of viral encephalitis, verified on Cerebrospinal Fluid (CSF) examination and necessary laboratory investigations were included as per inclusion and exclusion criteria. CSF was examined for HSV by PCR assays. The global outcome was determined in all patients with Glasgow Outcome Scale (GOS) at three months interval.GOS Score 1-3 were considered as poor outcome. Results: Median age of the included patients was 30 years (Range 1-70 years) with a male to female ratio 1.1:1 Besides fever (100%) confusion (92.1%) seizure (73.7%) and abnormal behavior (52.6%) were the prominent presenting features. Mean Glasgow coma scale score at admission was 10.37 (±3.17). Mean interval of CSF collection from the symptoms onset was 6.16 (±2.59) days. Out of 38 Patients 4 (10.5%) were positive for HSV type 1 and other 34 (89.5%) had negative PCR for HSV. Four patients were lost in follow-up so, 3 months mortality data were available for 34 patients. The mortality rate was 25% (1/4) in patients with HSV encephalitis compared to 16.7% (5/30) in non-HSV encephalitis. Twenty two patients (64.8%) had favorable outcome and 12 (35.2%) had poor outcome at 3 months. A multivariate analysis identified GCS score at presentation, presence of focal neurological deficit and delay in CSF collection to be independently associated with poor outcome. There was no significant difference in clinical feature, CSF findings and outcome between HSE and non-HSE patients. Conclusion: In the current study, 10.5% of cases encephalitis was diagnosed as having HSV. Disability persisted in 23.5% of total patients till 3 months. JCMCTA 2020 ; 31 (2) : 69-74